QUALITY OF LIFE, OBESITY AND CORPORATIVE FITNESS (Fiep Bulletin - online, 2014)
Obesity is a major problem of public health and its prevalence is rising across the world. Studies point to the negative impact that obesity has on physical functioning Objective: The aim of this study was to assess quality of life in overweight and obeses individuals enrolled on a health promotion program. Methods: 190 men (42,5  9,0 years) and 56 women (42,8  8,8 years) participated of this study. Quality of life was assessed using the questionnaire WHOQOL-bref, according its four domains: physical, psychological, social relationships and environment. Body Mass Index (BMI) was calculated as weight in kilograms divided by height in meters squared. Statistical analysis was performed using the software SPSS 13.0. Descriptive analyses is represented by mean and standard deviation. Analysis of variance (ANOVA) and Tukey test was used to compare WHOQOL-bref scores among BMI subgroups. Level of significance was 0,05. Results and Discussion: 60% of the sample present weight excess. The prevalence of obesity was 15,7% among men and 21,4% among women.The poorest score was seen in the physical domain, in women and men. The obesity did not determine expressive differences regarding the individuals with BMI normal. Conclusion: The results did not show an evident impact of the obesity in the quality of life of the obese individuals.This fact can be resulting of the insertion and adhesion of these individuals to the programs of physical activity and dietary advice offered by the CHP. Subsequent studies are necessary for verify this  hypothesis.
Keywords: Quality of life; WHOQOL-bref; obesity